Romanul Arhanghelii și „epoca de aur” a mineritului din Țara Moților - Alexandru Dumitriu (Revista de Istorie și Teorie Literară)
This study is part of a more thorough research paper, dedicated to a literary history of the Romanian mining. The organization of the paper is one based on “stratification”, starting from an industrial geography which trigerred a prosperous cultural and literary geography. Thus, the research paper will focus on the areas where a mining tradition developed, later on to be “imported” into literature. Such a territory is Țara Moților. The writer who established this topos is Ion Agârbiceanu, in his novel The Archangels from 1913–1914, the first literary work of such magnitude dedicated to the Romanian mining. The novel was initially published in instalments, in the “Luceafărul” literary magazine (Sibiu) in 1913. As a book, it was published in 1914, also in Sibiu. The novel homogenizes several approaches: mythological and ethnographic, parabolic (here, in its biblical meaning), and social and economic, all this forming a powerful realistic novel “about the life of the Romanians from Transylvania” – as, otherwise, is the subtitle of The Archangels in the first edition, since Transylvania was, in 1914, part of the Austro-Hungarian Empire. Agârbiceanu’s novel is, as mentioned above, the first literary work of a real magnitude, which “exploits” the local mining. Between 1906 and 1910, Agârbiceanu was a priest in the Bucium-Sașa parish, near Abrud. Mining was the main activity of the inhabitants at that time,. The priestly mission in Bucium-Sașa, albeit marred by certain shortcomings, given the parish was a poor one, provided the writer with an entire world. Speaking about the genesis of The Archangels, Agârbiceanu confessed in 1932: „The characters are almost entirely based on reality, only the story itself, the bountiful life, these happened about three or four decades before my going into the Apuseni Mountains. But there were still people who had known that bountiful life, and they were happy to tell about it”. It is the “golden age” of mining in Țara Moților, an age that was to be recreated on a large scale by Agârbiceanu in The Archangels. While affected by moral and didactic messages and haunted by echoes of the literary current know as “Sămănătorism”, the universe of the miners from Țara Moților has, in this novel, a s literary representation, surpassing the works of Alexandru Ciura, a prose writer from Abrud, which do have a monographic importance, and opening a gallery later ventured into by writers such as Geo Bogza, Aron Cotruș or Vasile Copilu-Cheatră.